Customers’ Buying Behaviour in Relation to Online Food Delivery (Evidence from National Capital Region (NCR) of India) (International Journal of Latest Technology in Engineering Management & Applied Science, 2026)
The growth of e-commerce, Digital India initiatives and the changing urban lifestyle of the Indian consumers are the drivers for online food order services. The seamless delivery of food at the doorstep with few clicks influence the Indian Consumers to order their favourite cuisines online from the restaurant of their choices. Companies look ahead huge potential in e-food industry segment and came up with food aggregator apps. The aim of this study is to determine the effect of huge discounts on LifeTime Value and buying behaviour of customers. The primary objective is to know the effect of discounts and services provided by the apps on the customer lifetime value. The secondary objective is to know the consumer perception towards different online food ordering apps and effect of discounts on buying behaviour of consumers.